Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (United Nations Commission on International Trade, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Anjarwalla Collins & Haidermota, 2025)

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (The Cairo Regional Centre for International Commercial Arbitration, 2024)

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

Etude sur les mécanismes de justice coutumière et les modes alternatifs de règlement des conflits au Burkina Faso - Moriceau, Julien; Ouattara, Fako; Bangali, Lamissa (Ministère de la Justice et des Droits humains, chargé des Relations avec les Institutions, 2023)
Keywords: Burkina Faso; Justice coutumière; MARC ( mode alternatif de réglement des conflits ); MARD

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

Lignes directrices de l'UA sur l'élaboration d'accords bilatéraux de travail (ABT) - Comité Technique Spécialisé sur le Développement Social, le Travail et l’Emploi (Union Africaine, 2022)

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes - Drličková, Klára; Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

Les sociétés coopératives d’intérêt collectif (SCIC) et les coopératives d’activité et d’emploi (CAE) - Pelosse, Hélène; de Crevoisier, Louis; Branchu, Christine; Muscatelli, Aude (Inspection générale des Finances, 2021)

Enjeux juridiques du télétravail transfrontalier - Chikoc Barreda, Naivi; Bernstein, Stéphanie (Conseil de recherches en sciences humaines, 2021)
Le télétravail transfrontalier, une pratique qui se développe depuis plusieurs années dans le contexte du processus accéléré de numérisation de l'économie et qui a reçu une impulsion incontestable en raison de la pandémie mondiale de COVID-19, se profile comme une tendance d’avenir. La dématérialisation du lieu de travail entraînant par essence un effacement des barrières spatiales, la prestation de travail exécutée à distance se déplace en continu à travers les frontières nationales par le biais des technologies de l'information et de la communication. La modification transfrontalière du domicile ou de la résidence du salarié pendant la durée du contrat est aussi une difficulté incontournable à laquelle sont confrontées les parties, un tel déplacement pouvant conduire au changement de régime applicable, sans que ni l’employeur ni l’employé en aient prévu cette conséquence. Face à ces problématiques, il s'impose d'examiner le cadre juridique applicable au télétravail comportant une dimension transfrontalière pour déterminer dans quelle mesure il permet de répondre aux principaux enjeux de cette pratique en expansion. Nous analysons les questions relatives à la détermination de l'autorité compétente pour connaître des litiges impliquant des télétravailleurs transfrontaliers et aux modes d’identification de la loi applicable parmi celles pouvant intervenir pour réglementer les droits et les obligations du travailleur et de l'employeur dans les rapports internationaux et interprovinciaux au Canada, ainsi que la façon dont les normes minimales d'emploi de l’Ontario, de la Colombie-Britannique, de l'Alberta et du Québec appréhendent le télétravail transfrontalier, leurs conditions territoriales d’application et leurs limites.
Keywords: Compétence internationale; Conflict of laws; Conflit de lois; Contrats internationaux; Lieu d'exécution du travail; Loi applicable; Mobilité internationale; Nomades numériques; Normes minimales d'emploi; Territorialité; Télétravail transfrontalier

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future - Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

Les entreprises et l'après crise de Covid-19 : un nouveau modèle d'organisation agile entre efficience et résilience - Sinapin, Marie Noeline (LITEM, Univ Evry, IMT-BS, Université Paris-Saclay, 2020)
Les entreprises traversent une crise sanitaire sans précédent, cette crise affecte sa survie et son organisation. Elle oblige les entreprises à se réinventer à faire preuve d'imagination pour transformer une menace en opportunité, et de devenir agile. Derrière cette crise de Covid-19, il est probable qu'une crise économique pointe ses contours: Chômage partiel, récession,faillite, récession et impacts directs et indirects inconnus.Comment surmonter cette crise d'un genre nouveau et résister à ses chocs imprévisibles ? Comment transformer l'entreprise et accompagner le changement ?Pour répondre à ces questions, les travaux de recherche autour du prisme de l'efficience et de la résilience peuvent-ils apporter des outils aux entreprises, afin de rebondir ?
Keywords: COVID-19; Efficience; Pandémie; Résilience

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)

How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (Washington DC, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

Rapport sur la situation économique en Mauritanie : améliorer le climat des affaires pour favoriser le développement du secteur privé - Banque mondiale (Groupe de la Banque mondiale, 2019)

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element - Drličková, Klára (Masaryk University Press, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (European Investment Bank, 2018)

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (European Investment Bank, 2018)

Bonne gouvernance et financement des sociétés coopératives en Côte d'Ivoire - Gbede, Jonathan (Friedrich-Ebert-Stiftung Côte d'Ivoire, 2018)
Menée sur une période de deux semaines, dans les localités de Grand-Lahou, Irobo, Dabou, Jacqueville, Songon, Sikensi, Elibou, Tiassalé, Agboville, Akoupé, Adzopé, Yakassé Att obrou, Aff éry, Bonoua, Bassam, Abidjan, Aboisso, Anyama, Bouaké, Yamoussoukro, Djébonoua, Mankono, Korhogo, Boundiali, Vavoua et Odienné, la présente étude vise à amener les sociétés coopératives à s’approprier les principes de bonne gouvernance dans leur quête de fi nancements.

L'intervention du juge dans la vie de la société en droit français et en droit OHADA - Mugisho Kazingufu, Jean-Jacques (Université de Goma, 2017)
Keywords: Corporate law; Droit des sociétés; Intérêt social; Règlement de conflits

Les enjeux de la déjudiciarisation - Cimamonti, Sylvie; Perrier, Jean-Baptiste (Mission de recherche Droit et Justice, 2017)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration - Drličková, Klára; Halla, Slavomír (Masaryk University Press, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

Réflexion sur la notion et le régime de la médiation au sein des modes amiables de résolution des différends : à partir des expériences de médiation dans les ressorts des Cours d’appel d’Aquitaine (Agen/Bordeaux/Pau), de Paris et de Lyon - Larribau-Terneyre, Virginie; Lecourt, Arnaud; Brus, Florence; Alvarez Elorza, Alexis; Drouiller, Camille; Sane, Claude MIchel (Mission de recherche Droit et Justice, 2017)

La cyberlégislation et réglementation comme moyen de renforcer le commerce électronique: études de cas et enseignements tirés de l’expérience - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Conseil du commerce et du développement, 2015)
Les transactions électroniques revêtent une importance croissante pour les pouvoirs publics, les entreprises et les consommateurs dans la plupart des pays. Le commerce électronique se développe, créant de nombreuses possibilités, mais se heurte encore à l’obstacle majeur qu’est le manque de sécurité et de confiance. La fraude en ligne et les atteintes à la sécurité des données suscitent des inquiétudes grandissantes et appellent des réponses législatives et réglementaires adéquates, qui permettent de faire croître le commerce intérieur et extérieur. Il n’est cependant pas facile d’adopter un cadre juridique et réglementaire satisfaisant, étant donné la variété et la complexité des législations et réglementations et l’évolution rapide des technologies et des marchés. Les nouveaux modes de paiement et le recours croissant à l’informatique en nuage rendent plus urgent encore le besoin de progrès dans ce domaine. La présente note porte sur les grandes questions juridiques dont il faut tenir compte pour faciliter le commerce électronique et améliorer la sécurité de la communication sur Internet en général. Elle passe brièvement en revue certaines des pratiques les plus indiquées pour surmonter les obstacles bien connus à l’élaboration et à l’application de la cyberlégislation, en prenant appui sur les activités que la CNUCED mène en liaison avec des groupements régionaux de pays en développement. On présente aussi dans cette note les résultats des travaux de la CNUCED sur les lois régissant actuellement ces aspects du commerce électronique, en soulignant les progrès accomplis et les lacunes à combler. On y réfléchit enfin aux moyens d’appliquer et de faire respecter efficacement les lois en vigueur en tenant compte des nouvelles technologies disponibles sur Internet et les appareils mobiles. Les politiques devraient viser à garantir la compatibilité des législations et à renforcer les capacités des principales parties prenantes, notamment les autorités chargées de faire respecter les lois.

Rapport sur l'amélioration du climat des affaires en Afrique Centrale - Commission Économique Pour l'Afrique (Bureau Sous Régional pour l'Afrique Centrale, 2014)

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Trade agreements and bilateral trade in sub-Saharan Africa: Estimating the trade effects of the EU-ACP PTA and RTAs - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
This paper on Trade Agreements within SSA, is an assessment of the ex post bilateral trade effect of the European Union-African Caribbean Pacific Preferential Trade Agreement (EU-ACP PTA) and sub-regional regional trade agreements (RTAs) on bilateral trade involving SSA countries. The main objective is to find out if EU trade preferences and regional trade agreements within SSA had increased trade flows. Estimating a gravity model augmented with measures of trade agreements, the paper made use of bilateral trade flows and key gravity covariates from CEPII database on 73 countries (48 SSA and 25 EU countries) over the period 1960-2006. After controlling for the endogeneity of the trade agreement dummy, accounting for multilateral price resistance and zero-valued trade flows, the findings indicate that the EU-ACP PTA and RTAs within ECOWAS and SADC have a positive and significant impact on bilateral trade involving SSA countries. In some cases the relative impact of the sub-regional RTAs was found to be stronger than the EU-ACP non-reciprocal PTA. The results therefore indicate the need for developing countries especially within SSA to focus on expanding and integrating regional markets in order to significantly improve trade performance.
https://www.econstor.eu/handle/10419/65446
Keywords: Bilateral Exports; Developing countries; Domestic Trade; Gravity Model; International Trade; Sub-Saharan Africa; Trade Costs

Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
https://www.econstor.eu/handle/10419/65470
Keywords: Bilateral Exports; Gravity Model; Sub-Saharan Africa; Trade Costs

La cession de contrôle en droit international privé [Conflict-of-law Rules in Conflict and Competition with Substantive Law Rules: The Case of Corporate Acquisitions] - Kerhuel, Anne-Julie (Georgetown University, 2010)

Migration de travail et protection des droits humains en Afrique : Les obstacles à la Convention Internationale sur la Protection des Droits de tous les Travailleurs Migrants et des Membres de leur Famille en Afrique subsaharienne - Sall, Babacar (UNESCO, 2007)
Les mouvements migratoires constituent de nos jours le nœud gordien de la problématique africaine, tant les facteurs générateurs de ces dynamiques sont incessamment alimentés par les crises politiques, économiques et démographiques. La question de la rareté ou de l’abondance des ressources, de la répartition des pôles de richesse sont autant d’éléments explicatifs de ces dysfonctionnements. C’est pourquoi la maîtrise des flux reste au cœur des préoccupations des États. Le continent africain compte de nos jours 20 millions de travailleurs migrants, mus par une migration de travail qu’il faut distinguer du phénomène conjoncturel des réfugiés. Cet effectif va en croissant au gré de la conjoncture économique et sociale et de l’instabilité politique. Rien qu’en Afrique de l’Ouest (hors Nigeria) près de 40 % de la population ne réside plus dans sa localité d’origine. Cela entraîne au sein des pays d’accueil de nombreux problèmes préjudiciables aux migrants de travail : exclusion, xénophobie, lois et règlements discriminatoires, etc. Le problème crucial qui se pose alors est comment garantir à cette frange vulnérable leurs droits fondamentaux au sein d’espaces d’accueil hostiles. L’objectif fixé dans le cadre de ce rapport consiste à étudier les conditions pour une ratification de la Convention internationale pour la protection des travailleurs migrants et des membres de leur famille, à la lumière des violations dont ces derniers font l’objet dans les pays d’accueil. Pour ce faire, quatre pays ont été choisis (Le Gabon, le Niger, le Cameroun, le Bénin) afin d’analyser de près les politiques migratoires en œuvre et leur articulation éventuelle avec ladite Convention. Ces pays ont en commun le fait de n’avoir pas encore ratifié la Convention. Il s’agira d’identifier dans chaque cas les facteurs qui peuvent entraver ou concourir à une future ratification à la lumière de la situation des travailleurs migrants dans les pays d’accueil respectifs, de leurs statuts, de la manière dont ils sont traités institutionnellement, des difficultés éventuelles qu’ils peuvent rencontrer dans l’exercice de leurs activités ou dans le cadre de leur séjour ainsi que celui de leur famille.

The Social Dimension of Regional Integration in ECOWAS - Robert, René (Social Science Research Network, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
10.2139/ssrn.908485
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

Cooperation Without Enforcement? A comparative analysis of litigation and online reputation as quality assurance mechanisms - Bakos, Yannis; Dellarocas, Chrysanthos (Massachusetts Institute of Technology Sloan School of Management, 2003)
Online reputation mechanisms are emerging as a promising alternative to more established mechanisms for promoting trust and cooperative behavior, such as legally enforceable contracts. As information technology dramatically reduces the cost of accumulating, processing and disseminating consumer feedback, it is plausible to ask whether such mechanisms can provide an economically more efficient solution to a wide range of moral hazard settings where societies currently rely on the threat of litigation in order to induce cooperation. In this paper we compare online reputation to legal enforcement as institutional mechanisms in terms of their ability to induce cooperative behavior. Furthermore, we explore the impact of information technology on their relative economic efficiency. We find that although both mechanisms result in losses relative to the maximum possible social surplus, under certain conditions online reputation outperforms litigation in terms of maximizing the total surplus, and thus the resulting social welfar
Keywords: E-commerce; Game Theory; Information Technology; Internet; Litigation; Online Reputation Mechanisms; Quality Assurance

Les modes alternatifs de règlement des conflits - Rivier, Marie-Claire; Ancel, Pascal; Blanc, Gérard; Cottin, Marianne; Gout, Olivier; Haubry, Xavier; Lawson-Body, Latékoué; Pourret, Jean-Louis; Sayn, Isabelle (Centre de Recherches Critiques sur le Droit, 2001)
La recherche effectuée a conduit à examiner comment les modes alternatifs de règlement des conflits (MARC), a priori nouveaux dans le droit français, ont été intégrés dans le discours des juristes, tel que tenu dans un ensemble de publications sélectionnées. Le dépouillement a permis l'établissement de 88 fiches concernant les ouvrages, et de 336 fiches s'agissant des revues. L'étude de cette masse documentaire, représentative du réseau de publications par lesquelles les juristes présentent, analysent le droit et contribuent à le faire, a montré comment la formule de "modes alternatifs" est entrée dans le discours doctrinal, mais aussi l'hétérogénéité des termes et des sens que recouvre cette formule. Quant au contenu du discours, on constate des constantes (un discours "de mode" et un discours "de crise") et des variantes dans l'appréciation portée sur cet objet. Loin de voir dans le développement des modes alternatifs de règlement des conflits une raison de remettre en cause leur activité et leur rôle, les juristes français ont intégré cet objet, recouvrant pour l'essentiel des mécanismes juridiques classiques, dans leurs analyses, et pour chacun des secteurs du droit concerné, l'ont situé dans un débat préexistant. La recherche de définitions, la (re)construction de catégories juridiques, l'élaboration d'un régime, sont autant de questions aujourd'hui considérées comme part intégrante de toute présentation de la justice ou des appareils judiciaires. Le discours tenu par les juristes tend aujourd'hui à privilégier l'examen technique de questions, situées dans le contexte d'une évolution caractérisée par la contractualisation, la procéduralisation du droit. Cette évolution, et non révolution, est désormais, dans la majorité des cas, présentée comme un phénomène irréversible.